Kinetics and sub sieve morphology of ball mill grinding for different grades of Indian coals. (2018) - Johar, R. Keshav; Saravanakumar, G.; Prasad, R. Krishna
The interactions of various factors affecting the ball mill grinding such as diameter of the ball, particle size and grinding time were studied. The kinetics of grinding on 80% passing size of product d80 was studied for two grades of coal namely lignite and bituminous using Box-Behnken method of surface response experiment. The bond grindability index and work index of the ball mill were determined. The variation in specific rate of breakage with ball diameter and number of balls was studied. The study on power consumption was done by varying the number of balls, ball diameter and grinding time. It was observed that the breakage was better for more balls with increase in ball diameter. The sub sieve morphology of particles in sieve was analysed using scanning electron microscopic observations to determine the breakage characteristics. [Received: March 8, 2016; Accepted: July 17, 2016]